The Influence of Perceived Credibility, Perceived Ease of Use, and Perceived Usefulness toward Customer Satisfaction in Using BSGtouch - Dominika R. Londa; Frederik G. Worang; Fitty V Arie (Universitas Sam Ratulangi, 2022)
Mobile banking is the result of the banking industry revolution that brings convenience, credibility, ease of use, timeliness and banking experience at the fingertips of its users. The advantages of mobile banking services increase customer satisfaction while the access of mobile banking as a customer transaction service delivery channel creates value for the bank. This research aims to analyze the customer satisfaction in using mobile banking through factors such as perceived credibility, perceived ease of use, and perceived usefulness, which focuses on mobile banking service of PT. BANK SULUTGO. This study describes causal research using quantitative approach. Questionnaires were distributed to 105 respondents who met the purposive sampling criteria in this research. The data are processed using Partial Least Square - Structural Equation Modeling (PLS-SEM). The results indicate that there is significant positive effect of perceived credibility, perceived ease of use, perceived usefulness toward customer satisfaction in using mobile banking. To compete digitally and survive, BSG needs to keep up with consumer expectations which will result to the customer satisfaction by providing guaranteed security and simplifying its digital platform by making it easier to use, so that its mobile banking will be evolving alongside consumer needs and user preferences.